`3/10 -(-5/8) =3/10 +5/8 =3/(2*5) +5/(2*4) =(3*4)/(2*4*5) +(5*5)/(2*4*5) =(12+25)/40 =37/40`

First step in solving is to observe the sign rule: two minus signs make one plus sign. Then we decompose the numbers under the line (the different denominators) of fractions in such a way as to observe their common multiple. Third step is to bring to a common multiple the numbers under the fraction line (the denominators) by amplifying both fractions with the missing terms. Thus we can consider we have a single fraction with an addition sign in the numerator. Last step is to add the numbers above the line of fraction to obtain the numerator of the fraction.

**Answer: 3/10 -(-5/8) =37/40**

Solve `3/10 - (-5/8).`

When subtracting fractions find the least common denominator. (The lowest multiple of 8 and 10. This is 40.

Rewrite equivalent fractions as 40th's.

`3/10 = 12/40`

`5/8 = 25/40`

Subtraction means to add the opposite therefore we will rewrite as:

`12/40 + (25/40)` = `37/40`

**The solution is `37/40.` **

3/10 - (-5/8)

To solve this the first thing that needs to be done is to open the brackets then find the LCM of 10 and 8,

3/10 + 5/8

Taking LCM of 10 and 8 which is 40, therefore 3 and 10 will be multiplied by 4 and 5 and 8 will be multiplied by 5,

3/10 * 4/4 + 5/8 * 5/5

12/40 + 25/40

(12 + 25) / 40

**37/40 Answer.**

QUESTION:-

3/10-(-5/8)=?

SOLUTION:-

`3/10-(-5/8)`

First open the bracket, for that we know the rule when 2 minus signs are multiplied with each other, we get a plus sign. Therefore,

`=3/10+5/8`

Find the LCD of 8 and 10. In this problem the lowest common denominator is 40, therefore,

`=3/10*4/4+5/8*5/5`

`=12/40+25/40`

`=(12+25)/40`

Add;

`=37/40`

Hence the answer of this problem is 37/40.

Hence it is Solved!